Molecular Characterization of Entomopathogenic Fungi Aspergillus amstelodami as a Bio control agent of Tick Infestation in Cattle - Jumade , Pratibha; Pal, S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Tick and tick borne diseases affects the production performance of animals ultimately results in economic losses to livestock owners. Tick control using chemicals producing acaricidal resistance and environmental pollution. To overcome this the study was conducted to introduce the biological control agents in the form of entomopathogenic fungi (EPF) isolated from naturally infected ticks. The molecular characterization of EPF species Aspergillus amstelodami isolated from naturally infected ticks of Durg district of Chhattisgarh was carried out by Polymerase Chain reaction (PCR) using internal transcribed spacer (ITS) gene as a molecular marker. The quality of DNA isolated from the culture was evaluated on 1.0% Agarose Gel with a single band of high-molecular weight DNA. Fragment of gene was amplified by PCR. The amplified PCR product was analyzed by agarose gel electrophoresis using 100bp ladder as a marker showed a single intense band corresponding to a 543 bp indicating successful amplification of gene from template DNA. DNA sequencing reaction of PCR amplicon was carried out with ITS1 primer using BDT v3.1 Cycle sequencing kit on ABI 3730xl Genetic Analyzer. The gene sequence was used to carry out BLAST with the NCBI Genbank database. The fungal isolate showed high similarity with Aspergillus amstelodami based on nucleotide homology and phylogenetic analysis. The evolutionary history was inferred using the Neighbor-Joining method. The confidence probability (multiplied by 100) that the interior branch length was greater than 0, as estimated using the bootstrap test (500 replicates was shown next to the branches. The evolutionary distances were computed using the Maximum Composite Likelihood method and were in the units of the number of base substitutions per site. The analysis involved 11 nucleotide sequences. Codon positions included were 1st+2nd+3rd+Noncoding.